2023
DOI: 10.1002/med.21939
|View full text |Cite
|
Sign up to set email alerts
|

Novel druggable mechanism of Parkinson's disease: Potential therapeutics and underlying pathogenesis based on ferroptosis

Abstract: Genetics, age, environmental factors, and oxidative stress have all been implicated in the development of Parkinson's disease (PD); however, a complete understanding of its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…The process of ferroptosis depends on iron ions and is characterized by three basic features such as the utilization of redox‐active iron, loss of lipid peroxide (LOOH) repair capacity and the oxidation of polyunsaturated fatty acid (PUFA)‐containing membrane phospholipids 17 . A growing body of evidence suggested that ferroptosis is associated with various human diseases, such as cancer, neurodegenerative diseases, infections and inflammation 18–20 …”
Section: Ferroptosismentioning
confidence: 99%
“…The process of ferroptosis depends on iron ions and is characterized by three basic features such as the utilization of redox‐active iron, loss of lipid peroxide (LOOH) repair capacity and the oxidation of polyunsaturated fatty acid (PUFA)‐containing membrane phospholipids 17 . A growing body of evidence suggested that ferroptosis is associated with various human diseases, such as cancer, neurodegenerative diseases, infections and inflammation 18–20 …”
Section: Ferroptosismentioning
confidence: 99%
“…Biochemical and transcriptomic analyses of mediators of iron metabolism, antioxidant defenses, oxidative stress, and lipid peroxidation in experimental disease models, autopsy material, and induced pluripotent stem cell (iPSCs) derived from patients indicate that ferroptosis is a major mechanism of cell death in a wide range of neurologic disorders. These include Alzheimer disease (AD), 64,72,76-82 Parkinson disease (PD), 55,83-87 amyotrophic lateral sclerosis (ALS), 88-92 Huntington disease, 93-95 Friedreich ataxia, 96-98 multiple sclerosis, 99-101 ischemic stroke, 47,102-105 intracerebral hemorrhage, 106,107 traumatic brain injury, 108 spinal cord injury, 109,110 epilepsy, 111-113 and glioma, 114 among others. This topic has been extensively reviewed, 16-21,115,116 and only few concepts will be emphasized in this study.…”
Section: Role Of Ferroptosis In Neurologic Diseasementioning
confidence: 99%
“…Both oxidative stress due to impaired mitochondrial complex I and decreased CoQ, GSH, and GPX4 levels and iron dyshomeostasis, reflected by increased TfR1 and DMT1 and decreased ceruloplasmin and ferritin expression, promote abnormal iron accumulation and ferroptosis in both dopaminergic neurons and glial cells. 28,83,125 α-Synuclein can form complexes with iron, act as a ferrireductase, and increase DMT1-mediated iron uptake in the cytosol. 126 In human dopaminergic neuron models, endogenous levels of α-synuclein can affect the availability of ether-linked phospholipids required for ferroptosis.…”
Section: Role Of Ferroptosis In Neurologic Diseasementioning
confidence: 99%
“…Ferroptosis is an iron dependent cell death form, which has attacked more and more attentions in PD pathogenesis (Chen and Xie, 2020;Jiang et al, 2023). Further investigations focused on the ferroptosis in these iron deposited brain regions of fear circuit may yield new mechanism and perspective for the development of anxiety in PD.…”
Section: A Commentary Onmentioning
confidence: 99%
“…In addition, changes of iron related proteins, which response for the iron import, iron storage and iron export, might occur in these brain regions of fear circuit during the development of anxiety in PD. Ferroptosis is an iron dependent cell death form, which has attacked more and more attentions in PD pathogenesis (Chen and Xie, 2020 ; Jiang et al, 2023 ). Further investigations focused on the ferroptosis in these iron deposited brain regions of fear circuit may yield new mechanism and perspective for the development of anxiety in PD.…”
mentioning
confidence: 99%